Investigating gender and achievement level differences in epistemological beliefs in physics - Derya Kaltakci-Gurel (Physical Review Physics Education Research)
This research investigated how freshman students’ epistemological beliefs in physics are impacted by gender and academic performance in a general physics course. Data were collected from 1220 university freshman students from 22 different programs in Türkiye. In this causal-comparative research, the well-known Colorado Learning Attitudes about Science Survey (CLASS) was used to assess students’ beliefs about physics and learning physics. A Turkish version of the CLASS, consisting of 20 items measuring problem-solving effort, conceptual understanding, and personal interest and real-world connection, was employed. Additionally, demographic data such as gender, cumulative grade point average (CGPA), and previous academic performance in the General Physics I Course were collected. Cronbach’s alpha coefficient for the reliability analysis of the whole scale was calculated as 0.844. The two-way between-groups multivariate analysis of covariance (two-way MANCOVA) test was used to answer the research question. The results indicated that gender and achievement level in the general physics course independently had significant effects on students’ scores on three CLASS survey subscales when their CGPAs were controlled. An inspection of the mean scores indicated that males showed higher scores in the three CLASS subscale scores than females. Additionally, high-achieving groups were found to have higher scores in the three subscale scores than medium-achieving and low-achieving groups. The results were discussed and suggested how the results could be applied to improve physics education.